(untitled) (International Journal of Innovative Technologies in Economy, 2019)
The article deals with the problem of debt borrowing in the context of a military conflict. It is proved that state borrowings play a significant role in the context of a sharp reduction of state budget revenues caused by military actions. The experience of countries in which military conflicts have reached a logical conclusion, as well as those where they are still ongoing (including in Ukraine) are considered. It is substantiated that the accumulation of public debt, in particular the external ones, during the war lays the basis for a long- term debt crisis in the country, which negatively affects the development of the economy as a whole. It is proved that under the conditions of intervention of the international community, the aggressor country may be compelled to pay compensation to the injured party. At the same time, the analysis of modern wars gives grounds to conclude that the vast majority of them are hybrid, and therefore, the country under such conditions will solve the problem of the debt crisis, mostly on its own, using its available resources (raw materials, natural, material, human, etc.).